Challenges of Commercializing Education in Nigeria in a Dwindling Economy: Implication on Educational Managers - Osaat, Dinah Sunday; Jack, I. F. (NIU Journal of Social Sciences, 2021)
This paper is a theoretical paper which examined the challenges of commercialising education in a dwindling economy in Nigeria. It described commercialisation as synonymous but with little difference to privatisation.  While privatisation is the process of transferring ownership and control of a government owned business to private individuals for profit maximisation, commercialisation means that the government while retaining ownership, will hand off the funding and management of those enterprises leaving them to tend for themselves with whatever expertise they may have. The paper highlighted the goals, types, rationale, positive and negative impacts of commercialisation. It also looked at the concept of dwindling economy and its characteristics. From the negative impacts of commercialisation of education, its challenges in the face of dwindling economy become obvious. Among others, is the hike and high rate of school fees to the level that if quality education is to be achieved through private institutions it therefore means that it is only for those who can afford leaving the less privileged in the hands of the mercy of God. The paper therefore recommended among others, that if every citizen is to enjoy quality education then the government should continue to take full risk and responsibility of giving quality education to her citizens for the betterment of our society and development. Keywords: Commercialization, commercialization of education, dwindling economy, management.